Applying characteristic mode analysis to finite antenna array design - Ludick, D.; Davidson, David (2016)
© 2016 IEEE. This paper considers the characteristic mode analysis (CMA) of finite antenna arrays, specifically for the design of the array element. The approach incorporates the Domain Greens Function Method (DGFM), i.e. a method-of-moments (MoM) based approach, to extract an active impedance matrix for each array element. The impedance matrices model the array environment for each antenna element and serve as input to an eigenvalue solver for the CMA. From here the eigencurrents and eigenvalues can be obtained that provide insight into the radiating properties of the elements in an active array environment.